A molecular model for the differential activation of STAT3 and STAT6 by the herpesviral oncoprotein tip. - Eman Dey Mazumder (Public Library of Science (PLoS), 2012)
Constitutive STAT signaling provides growth promoting signals in many forms of malignancy. We performed molecular modeling and molecular dynamics studies of the interaction between the regulatory Src homology 2 (SH2) domains of STAT3 and 6 with phosphorylated peptides of the herpesviral oncoprotein Tip, which facilitates Src kinase mediated STAT-activation and T cell proliferation. The studies give insight into the ligand binding specificity of the STAT SH2 domains and provide the first model for the differential activation of STAT3 or STAT6 by two distinct regions of the viral Tip protein. The biological relevance of the modeled interactions was then confirmed by activation studies using corresponding recombinant oncoproteins, and finally by respective recombinant viruses. The functional data give experimental validation of the molecular dynamics study, and provide evidence for the involvement of STAT6 in the herpesvirus induced T cell proliferation.